EVALUASI LELANG JABATAN DI LINGKUNGAN PEMERINTAH PROVINSI JAWA TENGAH TAHUN 2013-2014 (Studi Penelitian pada Eselon III dan IV di Dinas Bina Marga Dan Dinas Pemuda dan Olahraga) - Malio Adam Nurwana; Sulistyowati .; Nunik Retno Herawati (Journal of Politic and Government Studies, 2016)
Bureaucratic reform is an important thing in order to reach national development. The realization of bureaucratic reform in Indonesian government is the implementation of Open Biding which focuses to filling the positions of echelon III and IV in Department of Highways and the Department of Youth and Sports of Central Java province. In organizing the auction policy positions, there is some evaluation on every implementation of its selection process. Therefore the formulation of problem in this research is “How the realization of open biding is implemented in Department of Highways and the Department of Youth and Sports of Central Java province in order to fill the positions of echelon III and IV, what is the problem happened in the process of open biding, and how is the process of open biding evaluation implemented. The direction of this research is to obtain some information detailly about the mechanisms of implementation of the open biding that focuses on filling the post of echelon III and IV in the Department of Highways and the Department of Youth and Sports of Central Java and knowing the problems that happen in the implementation of the open biding selection. The research method is descriptive qualitative. Primary source data retrieved from interview and secondary data from document, archieve, and the other source which it is still connect with research. Analysis technique using qualitative data with analyst in form essay, depiction, and drawing the conclusion of indication research. From the result of research, showing that implementation of open biding that focuses on filling the positions of echelon III and IV in Department of Highways and the Department of Youth and Sports of Central Java province uses the concept of talent scouting to find talent pool who is worthy occupying some structural positions in the Government of Central Java Province.. In addition, the concept of talent scouting that is used in the post auction also impact on effectiveness and appropriate of the necessary of provincial government officials will be able to occupy technical positions are supported by the specification of skills and capabilities. The Regional Employment Board as the organizer of this policy should be able to monitor the performance of assessment center team more objective in doing the assessment of managerial competence. In addition, the Regional Employment Board should be more transparent in disseminating the results of the assessment to every department in Central Java in order to provide explanation detailly related to how the results of the selection which is followed by the entire of government employees from each SKPD and any indicator about criteria of participants who qualify and do not qualify to be will be an evaluation for all employe of government. Keyword: Evaluation, Open Bidin